2019
DOI: 10.4103/ijpsym.ijpsym_234_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in an Urban Geriatric Population in Marathwada Region of Western India

Abstract: Background: Depression is a common problem in the elderly but is often undetected and ignored as a medical problem, leading to poor quality of life. This community-based study was conducted to know the burden and risk factors of depression among the elderly. Subjects and Methods: The survey was done in 2015 in Maharashtra, India as a part of an initiative addressing community mental health needs of the elderly. Total 400 elderly, aged 60 years and above, were selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
4
8
1
Order By: Relevance
“…Advancing age is often accompanied by various events in life such as the death of a spouse, retirement, financial dependence, etc. Similar findings were observed by certain other studies [ 1 , 10 , 14 ]. However, Kavithai et al reported in their study that depression was more common among those aged below 80 years [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Advancing age is often accompanied by various events in life such as the death of a spouse, retirement, financial dependence, etc. Similar findings were observed by certain other studies [ 1 , 10 , 14 ]. However, Kavithai et al reported in their study that depression was more common among those aged below 80 years [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Aging being a normal multidimensional process is associated with physical, social, and psychological changes [ 1 ]. The four areas where the impact is being felt the most are health, economy, social and political, due to an aging population.…”
Section: Introductionmentioning
confidence: 99%
“…15 The result obtained in the study were similar with the study done by Buvneshkumar et al and other. [16][17][18] Similar findings were observed that depression was associated with increasing age, female gender, no formal education and lower educational status. 6,19,20 This may be said that as age increases physical competencies slower down consequently higher morbidities make them alienated from doing physical and other activity and they become more dependent on others for their daily needs, this in turn contribute to psychological depression.…”
Section: Discussionsupporting
confidence: 60%
“…The prevalence of depression among older adults in our study congruents with the study of Sangma et al and others. 15,17,21…”
Section: Discussionmentioning
confidence: 99%
“…Rathod et al [7] evaluated the prevalence of depression among the elderly population in Aurangabad district of Maharashtra. They had estimated the required sample size, used systematic random sampling, and screened the elderly persons using a translated version of Major Depression Inventory (MDI).…”
Section: Guest Editorialmentioning
confidence: 99%